2009
DOI: 10.1002/cnm.1226
|View full text |Cite
|
Sign up to set email alerts
|

The flow‐field downstream of a collapsible tube during oscillation onset

Abstract: SUMMARYThe flow-field immediately downstream of a collapsible tube during oscillation onset starting from the collapsed state was measured using two-dimensional high-speed particle image velocimetry. Both tube and fluid were chosen to produce oscillation at the lowest possible Reynolds number, of just over 300. The flow was examined in the plane formed by the tube axis extended into the downstream pipe and the major axis of the tube collapse cross-section. The resulting time-series of spatial fields of 2D velo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
1
8
1
Order By: Relevance
“…We also note that the character of the self-excited oscillations observed in the experiments of Bertram (e.g. Bertram & Tscherry 2006;Bertram et al 2008;Truong & Bertram 2009) is very different from those studied here. In particular, in Bertram's experiments (where the flow is driven by a prescribed pressure drop) the greatest fluctuations in the flow rate are observed in the downstream rigid tube.…”
Section: Discussioncontrasting
confidence: 83%
“…We also note that the character of the self-excited oscillations observed in the experiments of Bertram (e.g. Bertram & Tscherry 2006;Bertram et al 2008;Truong & Bertram 2009) is very different from those studied here. In particular, in Bertram's experiments (where the flow is driven by a prescribed pressure drop) the greatest fluctuations in the flow rate are observed in the downstream rigid tube.…”
Section: Discussioncontrasting
confidence: 83%
“…This is well in excess of the parameters used in the simulations in this paper, indicating that sufficiently large values of H can easily be realized experimentally. We wish to stress, however, that the character of the flow fields observed during self-excited oscillations in the experiments by Truong & Bertram (2009) with pressure-driven flows differs significantly from those observed in the computations presented here. In particular, the velocity perturbations induced by the wall oscillation were most pronounced in the downstream rigid tube, while the flow field in the upstream rigid tube remained virtually unaffected by the oscillations, suggesting that the oscillations observed in these experiments arise via a different mechanism.…”
Section: Summary and Discussionmentioning
confidence: 63%
“…In terms of the non-dimensionalization employed in this paper, this requires the material parameter H to be sufficiently large. Using the properties of the rubber tubes used in the experiments by Bertram & Elliot (2003) and Truong & Bertram (2009) (a = 6.5 mm, h = 1 mm, ν = 0.5 and E = 3.15 MPa) and assuming water (μ = 10 −3 kg (m s) −1 and ρ = 1000 kg m −3 ) as the working fluid, yields H = 5.38 × 10 7 . This is well in excess of the parameters used in the simulations in this paper, indicating that sufficiently large values of H can easily be realized experimentally.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The standard deviation of local time-averaged velocities across the exit was 5.4 and 13 % of the spatial average of the time-averaged local velocities for τ = 0 and 10 s, respectively. Prior work has shown that small jets can emanate from the lobes of the collapsed tube during self-excited oscillations (Bertram et al 2008;Truong & Bertram 2009). However, Bertram et al (2008) found that these jets can dissipate quickly due to viscous diffusion (at low Reynolds number).…”
Section: Laser Doppler Velocimetrymentioning
confidence: 99%